Results of an Intervention for Improving Arterial Hypertension Control in Four Health Areas - Addys Díaz Piñera; Armando Rodríguez Salvá; René García Roche; Isabel Carbonell García; Fernando Achiong Estupiñán (Revista Finlay)
Foundation: non-transmissible diseases represent one of the highest challenges for health and development in the XXI century. Arterial hypertension is a disease and a key risk factor fro developing other diseases. Objective: to show the results after the implementation of an educative intervention from promoting the control and management of arterial tension in four health areas. Methods: it was used a case and control study post- intervention during 2014 in four health areas, two belonging to the Santiago de Cuba municipality and two of Cardenas. A number of 1404 patients older than 18 years were studied, who were selected by bi-stage conglomerate sampling. Socio-demographic variables such as health area, age, sex, skin color, level of schooling, marital status and occupation were analyzed. The clinical variables analyzed were control of arterial tension, treatment compliance, and perception of the health condition, so as knowledge of the disease. The information was calculated in absolute numbers, percentages and confidence intervals of 95 %. It was evaluated the possible association among variables by the existence of the statistic significance (α= 0,05) by the Square-chi Pearson Test. Results: a higher percentage of controlled hypertensive patients was achieved (65,0 %) and with treatment compliance (64,9 %), the level of knowledge about the disease was increased (50,9 %) so as the perception of good health condition (67,2 %) in comparison to 2013. The results were more encouraging in the groups which were intervened. Conclusion: the program of intervention demonstrated to be effective at achieving the increase of levels of treatment compliance and patient controls.